2020
DOI: 10.1002/er.5120
|View full text |Cite
|
Sign up to set email alerts
|

Li‐doping stabilized P2‐Li 0.2 Na 1.0 Mn 0.8 O 2 sodium ion cathode with oxygen redox activity

Abstract: Summary The discovery of the oxygen chemistry phenomenon reveals bright future toward new sustainable layered Na‐based transitional oxides. However, the poor capacity retention problem of the cathode has hindered the development of sodium ion batteries (SIBs). In this work, a new Li‐doped compound Li0.2Na1.0Mn0.8O2 is proposed, which demonstrates refined cycling durability with 51.6% after 100 cycles at 50 mA g−1, superior than Na1.2Mn0.8O2 with only one cycle. Then in situ X‐ray diffraction (XRD) and density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Later on, enormous research efforts have been focused on doping strategies by incorporating two, three, or even more transition metal elements to obtain stable lattice structure and suppress the reactivity of the Jahn-Teller active Mn 3+ . The results showed that single-or multi-element doping by Li [61], B [62], Mg [63], Al [64], Ti [65], Fe [66], Co [67], Ni [68], Cu [69], or Zn [52] can improve the reversible capac-ity and cycling retention of NaMnO 2 . Among these materials, the primary structure is often either P 2 or O 3 based on the atomic arrangement.…”
Section: Sodium-layered Oxidementioning
confidence: 99%
“…Later on, enormous research efforts have been focused on doping strategies by incorporating two, three, or even more transition metal elements to obtain stable lattice structure and suppress the reactivity of the Jahn-Teller active Mn 3+ . The results showed that single-or multi-element doping by Li [61], B [62], Mg [63], Al [64], Ti [65], Fe [66], Co [67], Ni [68], Cu [69], or Zn [52] can improve the reversible capac-ity and cycling retention of NaMnO 2 . Among these materials, the primary structure is often either P 2 or O 3 based on the atomic arrangement.…”
Section: Sodium-layered Oxidementioning
confidence: 99%
“…Operando XRD also revealed that P2 materials can follow several different structural routes during cycling. Some maintain their structure during cycling (solid solution behaviour), [73,81,82,87] others reversibly transition into O2 phases, [69,80,86,104] a third group stop at disordered intermediate phases termed “Z‐“or “OP4” [68,77,83,95] . Jung et al .…”
Section: X‐ray Diffraction and Scatteringmentioning
confidence: 99%
“…Conversely [29,30] The superior cycle stability of Na[Li 0.2 Mn 0.8 ]O 2 was understood that Li substitution in M layers in the oxide decreased lattice instability induced by P2-O2 phase transition and stabilized the adjacent oxygen ions in restraining the irreversible anionic redox. [31,32] Also, Vergnet et al demonstrated that the P-type Na 2/3 Mg 1/3 Mn 2/3 O 2 was more stable than the O-type one in the stacking types point of view. [33] Recently [34] Remarkably, the study showed that the first material undergoes a reversible oxygen redox reaction without a large voltage hysteresis, compared with the latter oxide.…”
Section: Introductionmentioning
confidence: 99%
“…analyzed the charge‐compensation mechanism related to oxygen redox reactions during Na‐extraction in Li‐incorporated Mn oxide [29,30] . The superior cycle stability of Na[Li 0.2 Mn 0.8 ]O 2 was understood that Li substitution in M layers in the oxide decreased lattice instability induced by P2‐O2 phase transition and stabilized the adjacent oxygen ions in restraining the irreversible anionic redox [31,32] . Also, Vergnet et al .…”
Section: Introductionmentioning
confidence: 99%